How Common Are Lesions on the Tails of Sauropods? Two New Pathologies in Titanosaurs from the Late Cretaceous of Argentine Patagonia - Cruzado Caballero, Penélope (2023)
Studies of the paleopathology of the vertebrae provide an interesting, oblique approach to their paleobiology and even paleoethology. They tell us about possible ethological causes such as accidental blows with objects, social interactions within a group, and defense against predators, etc. There are numerous works on the anatomical and phylogenetic aspects of sauropod dinosaurs, and in recent years paleopathological studies have also increased. Here, we describe the injuries recorded in the caudal vertebrae of two indeterminate titanosaurids, and undertake a compilation and analysis of the pathological fossil record worldwide, focusing on the tails of sauropods. Two pathologies have been identified as present in the indeterminate titanosaurids under study: a possible case of spondyloarthropathy in MAU-Pv-LI-601, and a case of suppurative spinal osteomyelitis in MAU-Pv-LJ-472/1. Both titanosaurids are from Gondwana. In the world registry of pathologies associated with the tails of sauropod dinosaurs, it is observed that titanosaurs are the sauropods with the highest percentage of diagnosed pathologies (69% including the two new records from the province of Neuquén) and that all of these have been described in Gondwanan specimens.